Prevalence and risk factors of depression in Korean patients with untreated obstructive sleep apnea - Kim, Jeongsik; Park, Hea Ree; Joo, Eun Yeon; Seo, Dae-Won; Shon, Young-Min (Frontiers in Neurology, 2025)
IntroductionThis study investigated the prevalence and risk factors of depression among Korean adults with untreated obstructive sleep apnea (OSA).MethodsA total of 887 adults newly diagnosed with OSA at a university hospital underwent overnight polysomnography and completed validated Korean questionnaires assessing depression (BDI-II-K), insomnia (ISI-K), sleep quality (PSQI-K), and daytime sleepiness (ESS-K). Clinical depression was defined as a BDI-II-K score ≥17. Demographic, clinical, and sleep-related variables were compared between OSA patients with and without depression. Logistic regression identified independent risk factors, and factor analysis of the BDI-II-K explored symptom structure.ResultsClinical depression was present in 24.2% of OSA patients. The depression group had a higher proportion of women, older age, more frequent use of sleeping pills, and lower rates of regular exercise and employment. Polysomnography revealed longer sleep latency, lower sleep efficiency, and reduced N3 sleep in the depression group, but no difference in AHI severity or oxygen desaturation. Questionnaire data showed greater daytime sleepiness, more severe insomnia, and poorer sleep quality among depressed patients. Multivariable analysis identified higher arousal index (OR = 3.51), greater daytime sleepiness (OR = 1.36), and increased insomnia severity (OR = 5.27) as risk factors for depression, while AHI was not. Factor analysis indicated cognitive symptoms were most strongly associated with depression.ConclusionDepression is common in Korean patients with untreated OSA, with sleep fragmentation, insomnia, and daytime sleepiness as key risk factors. Cognitive symptoms predominate the depressive profile. Routine depression screening and integrated management addressing both sleep and mood disturbances are recommended for this population.